The Shapley value for shortest path games - Péter Miklós Pintér; Anna Radványi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
In this paper shortest path games are considered. The transportation of a good in a network has costs and benefit too. The problem is to divide the profit of the transportation among the players. Fragnelli et al (2000) introduce the class of shortest path games, which coincides with the class of monotone games. They also give a characterization of the Shapley value on this class of games. In this paper we consider further four characterizations of the Shapley value (Shapley (1953)'s, Young (1985)'s, Chun (1989)'s, and van den Brink (2001)'s axiomatizations), and conclude that all the mentioned axiomatizations are valid for shortest path games. Fragnelli et al (2000)'s axioms are based on the graph behind the problem, in this paper we do not consider graph specific axioms, we take TU axioms only, that is, we consider all shortest path problems and we take the view of an abstract decision maker who focuses rather on the abstract problem than on the concrete situations.
Keywords: C71; 330; TU games; Shapley value; Shortest path games; Axiomatizations of the Shapley value; Shapley-Wert; Spieltheorie